English App Developing English App Based Mobile Learning as the Innovation of English Learning Media - Anita Rahmah Dewi; Wilujeng Asih Purwani; I'anatul Avifah (IJET (Indonesian Journal of English Teaching), 2022)
Abstract. This research aims to develop learning media as the innovation English app in enhancing the process of teaching-learning English in 4.0 Era. Through this app, it can be integrated by hybrid learning model that is prepared to deal with post-pandemic era challenge. This research was conducted based on the results of needs analysis of current learning that cannot be carried out fully face-to-face, as well as needs students and educators towards effective learning media. The objectives of this research are to elaborate the process of designing and developing learning media English App based M-Learning and examine the feasibility of that media in learning process of General English Courses in University of Billfath. The research design used is Research and Development (R&D) by applying the ADDIE model with five stages: analyze phase; design; development; implementation; evaluation. In further, the result of this research points out that in analyze phase found 71,3 % college students requires specific learning media-based M-learning that can be applied in hybrid learning model. While in the process of design and development English App as has been validated by experts that describe material validation 88,5 % and media validation 89% that can be said that the product is valid and deemed to be implemented. The stage of implementation is conducted seven meeting by hybrid learning. Furthermore, in evaluation stage indicates that the product has been feasibility to be applied in English learning due to the result obtained 80,6% (valid product). Hence, Mobile English App that is developed for college students in learning English has been succeed in fostering students ‘motivation and ability in General English Course.